Facing the lion : growing up Maasai on the African savanna - Lekuton, Joseph; Viola, Herman J. (Washington, D.C. : National Geographic, 2003)
A member of the Masai people describes his life as he grew up in a northern Kenya village, travelled to America to attend college, and became an elementary school teacher in Virginia.
A lion hunt -- The proud one -- Cows -- The pinching man -- School -- Initiation -- Kabarak -- Soccer -- America -- A warrior in two worlds.
Keywords: Lekuton, Joseph -- Juvenile literature; Lekuton, Joseph; Maasai (African people) -- Kenya -- Biography -- Juvenile literature; Maasai (African people) -- Kenya -- Social life and customs -- Juvenile literature; Maasai (African people) -- Biography; Maasai (African people) -- Kenya -- Social life and customs; Blacks -- Kenya -- Biography